2021
DOI: 10.1038/s42003-021-02615-y
|View full text |Cite
|
Sign up to set email alerts
|

Venous puncture wound hemostasis results in a vaulted thrombus structured by locally nucleated platelet aggregates

Abstract: Primary hemostasis results in a platelet-rich thrombus that has long been assumed to form a solid plug. Unexpectedly, our 3-dimensional (3D) electron microscopy of mouse jugular vein puncture wounds revealed that the resulting thrombi were structured about localized, nucleated platelet aggregates, pedestals and columns, that produced a vaulted thrombus capped by extravascular platelet adherence. Pedestal and column surfaces were lined by procoagulant platelets. Furthermore, early steps in thrombus assembly wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(43 citation statements)
references
References 31 publications
7
36
0
Order By: Relevance
“…In this example, the exposure of vessel wall extracellular matrix proteins—for instance, collagen—leads to platelet anchoring to the exposed adventitia in the case of a vein or externa in the case of an artery. Subsequent platelet binding to the matrix-anchored platelets leads to the formation of platelet aggregates that have recently been termed pedestals and columns and leads to beading cessation by extravascular capping of the puncture hole [ 1 ]. The exact activation state of the newly recruited platelets, ie, how closely these platelets resemble the circulating platelets and to what platelet activation state the subsequent rounds of platelet capture produce is presently unknown owing to the lack of detailed ultrastructural data over volumes that are near millimeter dimension.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this example, the exposure of vessel wall extracellular matrix proteins—for instance, collagen—leads to platelet anchoring to the exposed adventitia in the case of a vein or externa in the case of an artery. Subsequent platelet binding to the matrix-anchored platelets leads to the formation of platelet aggregates that have recently been termed pedestals and columns and leads to beading cessation by extravascular capping of the puncture hole [ 1 ]. The exact activation state of the newly recruited platelets, ie, how closely these platelets resemble the circulating platelets and to what platelet activation state the subsequent rounds of platelet capture produce is presently unknown owing to the lack of detailed ultrastructural data over volumes that are near millimeter dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we take the “big data” image sets generated by our laboratories [ 1 ] and analyze them at a high resolution to solve points central to the pathway of thrombus formation in vivo . Previously, we had binned the data and used it at a relatively low resolution to establish vaulted thrombus formation in a jugular vein puncture wound model [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the SBF-SEM, it has been possible to image entire blood clots in a mouse model, where 3D ultrastructure can be obtained from volumes as large as 10 million cubic micrometers, albeit at lower zresolution perpendicular to the block-face. Unexpectedly, we have found that mouse jugular vein puncture wounds result in thrombi that are structured about localized, nucleated platelet aggregates, pedestals and columns, producing a vaulted thrombus capped by extravascular platelet adherence [8]. Despite the lower z-resolution in SBF-SEM, the spatial resolution in the block-face x,y-plane is sufficient to characterize the platelet activation state based on subcellular ultrastructure (Figure 2).…”
mentioning
confidence: 96%
“…With the emergence of 3D electron microscopy techniques of serial block-face scanning electron microscopy (SBF-SEM) [1,2] and focused ion beam scanning electron microscopy (FIB-SEM) [3,4] whereby backscattered electrons are collected from stained embedded biological specimens using 1-keV to 2-keV energy incident probes, it has become feasible to image cellular and tissue ultrastructure at a nanoscale. Each of these two approaches has advantages and limitations, which are illustrated here by an application in the field of hemostasis and thrombosis, where the techniques enable the investigation of blood platelet activation and clotting [5][6][7][8].…”
mentioning
confidence: 99%